Education Implementation in Realizing Sustainable Development - Suryadi, Ahmad (Institute Of Advanced Knowledge and Science, 2024)
This article discusses the implementation of education to realize sustainable development. This type of research includes qualitative research (library research). The results show that awareness to implement sustainable development is one of the solutions to overcome various problems that arise due to increased human activity. Thus, it is very important to implement education for sustainable development as early as possible. The combination of pedagogical techniques with PuPB content contributes to teaching creativity, critical thinking, and fostering a willingness to learn for life, as well as all the habits that will support the achievement of a sustainable society.